Houses and homes - Rickards, Lynne (Cambridge : Cambridge University Press, 2016)
People live in different homes. Find out more about them. In Red Band illustrations continue to support understanding but readers also need to use decoding skills. Slightly longer texts with less repetition extend high-frequency word knowledge. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Children's - readers; Juvenile - works